The cultivation of the character values of early childhood by parent - Syuraini Syuraini; Syafruddin Wahid; Zahratul Azizah; Alim Harun Pamungkas (Fakultas Ilmu Pendidikan UNP)
This research aims to know the description of model parent implemented character education at home. Research methods using R development model D with & ADDIE. The population of the research was the parents in Kindergarten of Aisyiyah at Padang city. Sampling techniques using cluster random sampling that is the center of the city, the suburbs and the city centre and suburbs. The instruments used are a test of the validity of using with cheklist construct and content validity. The results showed that generally how committed parents in educating children character is by way of conditioning, then followed by the rules. While other ways such as giving advice, and less is done by the parents. It is very possible because more parents emulating what has been done to his parents during this time.